Inculturação litúrgica e expressão do sagrado nos vitrais do padre Geraldo Leite Bastos. - Costa, Luís Ribeiro da (2023)
The transformations of the Second Vatican Council ushered in indispensable liturgical openings in the Church, fostering the emergence of a more contemporary religious art in the realms of architecture, liturgical music, and iconography. These changes aimed to assist the faithful in fully participating in the celebrations. It is within this context that Father Geraldo Leite Bastos was ordained as a priest in the Archdiocese of Olinda and Recife on December 8, 1961. The following year, he assumed the role of founding pastor of the Parish of Our Lady of Good Counsel in the Ponte dos Carvalhos village (1962-1980), in the city of Cabo de Santo Agostinho. In this seemingly impoverished and sterile environment, the ecclesial base community emerged as a precursor, affectionately named by Father Geraldo himself as the "Nation of the Divine." Beyond his ecclesiastical dimensions, Father Geraldo actively engaged in community life and, notably, developed his artistic skills using various forms of expression such as the construction of sacred spaces, composition of ritual music, theater, and the creation of stained glass as an integral part of an inculturated liturgy. Drawing deeply from the premises of Vatican II throughout his existence, Father Geraldo's influence can be measured by the insightful fragment from Souza (2008; p.88), explaining that "Nothing done during a liturgical action presided over by GLB was disconnected from reality. Everything stemmed from a concrete experience of life, from the community's daily life." By incorporating liturgy into his own life, he lived consistently with what he celebrated, creating no disintegration between the two. The presented work aims to describe the main theoretical aspects concerning contemporary aesthetic concepts that influenced the stained glass art of Father Geraldo Leite Bastos. It identifies and analyzes the official documents of the Catholic Church from the Second Vatican Council regarding liturgical inculturation and examines the symbolic elements that manifest the sacred through the signs arranged in the stained glass. This study contributes to the field of Religious Sciences and Theology (code 44 CAPES no. 174/2016) and explores a research area on visual culture, particularly focusing on stained glass as an imperative genre of religious art. Regarding theoretical frameworks, the study employs renowned authors in the history of art such as Gombrich (2013), Panofsky (2001-2017), Pastro (2010), and, specifically for stained glass, Vallderpérez (2000). In the realms of history and sociology, the work draws from Crosby (1993), Eisenberg (1977), Freyre (1967), Willaime (2012), and Berger (1985). For the philosophy of religions, Eliade (2000) and Grondin (2012), and in semiotics, Santaella (2004) are used. Methodologically, the analysis of these stained glass works relies on authors like Panofsky (2017), Gomes Filho (2003), and Costella (2002).